2003
DOI: 10.1051/0004-6361:20030005
|View full text |Cite
|
Sign up to set email alerts
|

New infrared star clusters in the southern Milky Way with 2MASS

Abstract: Abstract. We carried out a 2MASS J, H and K s survey of infrared star clusters in the Milky Way sector 230• < < 350• . This zone was the least studied in the literature, previously including only 12 infrared clusters or stellar groups with |b| < 10• , according to the recent catalogue by Bica et al. (2003). We concentrated efforts on embedded clusters, which are those expected in the areas of known radio and optical nebulae. The present study provides 179 new infrared clusters and stellar groups, which are int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
243
1
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(256 citation statements)
references
References 35 publications
(56 reference statements)
7
243
1
4
Order By: Relevance
“…With the advent of 2MASS (Cutri et al 2003), systematic searches for embedded star clusters became possible. A similar search to the one performed in the optical, but now over the infrared cluster catalogues of Bica et al (2003) and Dutra et al (2003), only reveals two more pairs. Another exercise than can be done is to search over the merged list of optically revealed and hidden clusters.…”
Section: Cluster Samplementioning
confidence: 76%
“…With the advent of 2MASS (Cutri et al 2003), systematic searches for embedded star clusters became possible. A similar search to the one performed in the optical, but now over the infrared cluster catalogues of Bica et al (2003) and Dutra et al (2003), only reveals two more pairs. Another exercise than can be done is to search over the merged list of optically revealed and hidden clusters.…”
Section: Cluster Samplementioning
confidence: 76%
“…However, it is likely that we uncovered the most populous objects. In the recent compilation of stellar clusters, updated to August 2011 of all Galactic star cluster catalogs (e.g., Dias et al 2002;Mercer el at 2005;Dutra et al 2003;Bica et al 2003;Borissova et al 2011), Morales et al (2013) counted 2247 clusters visible in the optical and 1950 and 197 cluster candidates found in the near-and mid-infrared, respectively. Since then, Solin et al (2012Solin et al ( , 2014, Majaess (2013), and Zasowski et al (2013) reported 137; 88; 229 and 20 new embedded cluster candidates in the UKIDSS GPS, VVV, WISE, and Spitzer GLIMPSE-360 areas.…”
Section: Cluster Search and Methods Of Analysismentioning
confidence: 99%
“…Besides serendipitous discoveries and findings in specific directions such as those of molecular clouds (Hodapp 1994) or nebulae (Dutra et al 2003a, hereafter Paper I), systematic methods can be applied: visual inspections of a whole area (Dutra & Bica 2000a) or automated methods (Reylé & Robin 2002;Ivanov et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The search in this zone complements that in the Southern Milky Way (Dutra et al 2003a). The method concentrates efforts on the directions of known optical and radio nebulae.…”
mentioning
confidence: 99%